Riding under the influence: unravelling substance abuse patterns among motorcyclists in South-Eastern Nigeria - Anigwe, Francis Chibuike; Mbanuzuru, Ahoma Victor; Obi-Okaro, Alphonsus Chukwuemeka; Edeh, Gabriel Chidera; Awugosi, Michael Chukwuebuka; Akwuobi, Glory Uchenna; Emmanuel, Samuel Ifeanyi; Ugwuanozie, Chioma Faustina; Anisiobi, Promise Ugochukwu (International Journal of Research in Medical Sciences, 2024)
Background: Drug and substance abuse has been outlined as a worldwide problem that is wreaking havoc on both social and public health across many nations. It is a global problem that affects both developed and developing countries. The objective of this study was to assess substance abuse among Okada riders in Nnewi, Anambra State, Eastern Nigeria. Methods: Drug and substance abuse has been outlined as a worldwide problem that is wreaking havoc on both social and public health across many nations. It is a global problem that affects both developed and developing countries. The objective of this study was to assess substance abuse among Okada riders in Nnewi, Anambra State, Eastern Nigeria. Results: About 221 Okada riders were assessed. Majority of them were middle aged. The mean age of the respondents were 39.5±11.1 years, with a range of 19-65 years. About 100% of the respondents were aware of substance abuse. Overall 73.3% of the respondents abuse at least a substance, with alcohol recording the highest use with 93.8% prevalence. About 77.2% of the abusers have taken these drugs before driving, and 65.2% have been involved in an accident, however only 5.4% admitted it was as a result of substance used. Conclusions: The prevalence of substances use among Okada riders in Nnewi was high. There was however a high awareness of the negative consequences of use of substance. Non-governmental organizations should target Okada riders for interpersonal communication interventions to help mitigate the use of substances.